GROUNDWATER TAX AS A REGULATORY INSTRUMENT: SUPERVISION STRATEGIES FOR CONTROLLING NEGATIVE ENVIRONMENTAL EXTERNALITIES IN DKI JAKARTA - Azka, Jasmine Serena; Ashidiqi, Zakky; Subagio, Aulia Tazkia (UTSAHA: Journal of Entrepreneurship, 2025)
Groundwater tax (PAT) functions as a dual-purpose regional fiscal instrument that serves not only as a revenue source but also as a regulerend policy tool to control excessive groundwater extraction. The phenomenon of land subsidence in DKI Jakarta, particularly in northern areas, demonstrates the critical need for more effective supervision of groundwater utilization. This study aims to analyze the implementation of groundwater taxation in Indonesia, examine groundwater usage patterns in DKI Jakarta, and investigate supervision strategies that regional governments can employ to prevent negative externalities. The research employs a qualitative approach utilizing literature review methodology. Data were obtained from legislative regulations, government agency reports, Central Statistics Agency publications, and previous research findings. Analysis was conducted using descriptive-analytical methods, emphasizing the interconnections between regional taxation, environmental management policies, and international best practices. Results indicate that PAT implementation in DKI Jakarta remains suboptimal due to persistent challenges including taxpayer compliance issues, weak inter-agency coordination, and limited supervision resources. Comparative analysis with the Netherlands and Germany reveals that technology-based supervision systems, self-monitoring mechanisms, and revenue allocation for water conservation can enhance regulatory effectiveness. This research concludes that regulatory strengthening, improved transparency, and digital technology utilization are essential for reinforcing PAT's role as an equitable and sustainable regulerend instrument.